Amyotrophic Monoplegia Secondary to Posttraumatic Rupture of the Brachial Plexus’s Roots: A Case Report and Review of the Literature - Oumniya Abouhanine; Hasnaa Belgadir; Vianney Ndayishimiye; Omar Amriss; Aicha Merzem; Nadia Moussali; Naima El Benna (Case Reports in Radiology)
Brachial plexus lesions most often occur in multiple trauma. We report a case of a 37-year-old patient who presented an upper left limb total sensitivomotor deficit and amyotrophy after a cervical and upper limb trauma. Cervical magnetic resonance imaging (MRI) was performed. It noted pseudomeningoceles at the levels of C6-C7, C7-D1, and D1-D2 in T1 hyposignal , T2 and STIR hypersignal , not enhanced by the injection of Gadolinium extending in foraminal and extraforaminal spaces without visualization of the corresponding rootlets. Traumatic brachial plexus injury is a potentially serious debilitating injury which can be well explored on MRI.